2021
DOI: 10.18488/journal.ajard.2021.113.222.229
|View full text |Cite
|
Sign up to set email alerts
|

Market-Based Strategy to Anticipate Covid-19 Pandemic in Smallholder Rubber Plantations in Riau Province, Indonesia

Abstract: The coronavirus pandemic had disrupted almost all businesses in various sectors, one of which is the plantation sector. Smallholder rubber plantations in Riau Province, Indonesia have faced the very tough challenges of the coronavirus pandemic. Efforts that could be made were marketing rubber products by implementing market-based strategies, namely market strategy, marketing mix strategy, customer value and marketing performance. This study aimed to analyze the effects of market strategy, marketing mix strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Rubber plantations are the primary source of the rural economy, so increasing the farmers' economy is necessary by increasing commodity prices [31]. Overcoming the weak bargaining position of farmers, Riau implemented a marketing strategy based on the auction market [32]. Farmers' bargaining position is stronger if sales are made directly, not through intermediaries [33].…”
Section: The Problem Of Declining Rubber Prices In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Rubber plantations are the primary source of the rural economy, so increasing the farmers' economy is necessary by increasing commodity prices [31]. Overcoming the weak bargaining position of farmers, Riau implemented a marketing strategy based on the auction market [32]. Farmers' bargaining position is stronger if sales are made directly, not through intermediaries [33].…”
Section: The Problem Of Declining Rubber Prices In Indonesiamentioning
confidence: 99%
“…In an association, Indonesia's only rubber marketing institution is Kuantan Singingi-Riau Regency. Overcoming the weak bargaining position of farmers, Riau implemented a marketing strategy based on the auction market [32]. As a result, the Kuantan Singingi Rubber Farmers Association conducts joint auction rubber sales centrally in the Regency.…”
Section: Institutional Efforts As Solutions To Improve Bargaining Pos...mentioning
confidence: 99%
“…Lokasi lahan petani yang jauh dari pabrik menimbulkan biaya produksi dan distribusi. Masalah-masalah ini dapat diatasi dengan menerapkan strategi pasar dan strategi bauran pemasaran (Khaswarina et al, 2021).…”
Section: Pendahuluanunclassified
“…Thus, if the price offered to the buyers cannot cover the cost, small farmers' productions might be affected, leading to difficulty achieving economic, environmental, and social sustainability performance. Khaswarina, Sucherly, Kaltum, and Ariawaty (2021) showed that if the price received by farmers were high, the farmer would be motivated to produce in large quantities. This study indicates that pricing strategy in the marketing mix had a significant relationship with performance.…”
Section: The Effects Of Pricing On Small Farmer Sustainability Perfor...mentioning
confidence: 99%